2011
DOI: 10.1247/csf.11004
|View full text |Cite
|
Sign up to set email alerts
|

DREF is Critical for Drosophila Bristle Development by Regulating Endoreplication in Shaft Cells

Abstract: ABSTRACT. DREF (DNA replication-related element-binding factor) plays important roles in replication and proliferation in vivo by regulating transcription of various genes. However, due to a lack of appropriate cell biological studies in vivo, roles of DREF during a single cell development are poorly understood. To address this question, we focused our attention on macrochaetes bristle development system. Utilizing cell lineage analysis focusing on a single posterior scutellar (PSC) macrochaete sensory organ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…A recent publication (44) has shown that DREF depletion in the notum and in other subdomains of the wing disc reduces or eliminates bristles. This phenotype is due in part to the influence of DREF on PCNA gene expression and affects the endoreplication process of bristle development, which results in a lack of bristles.…”
Section: Resultsmentioning
confidence: 99%
“…A recent publication (44) has shown that DREF depletion in the notum and in other subdomains of the wing disc reduces or eliminates bristles. This phenotype is due in part to the influence of DREF on PCNA gene expression and affects the endoreplication process of bristle development, which results in a lack of bristles.…”
Section: Resultsmentioning
confidence: 99%
“…4) were obtained by dividing the number by the total number of the observations. Shaft and socket cells were identified by size, shape and location as previously described [30].…”
Section: Methodsmentioning
confidence: 99%
“…To determine this, we carried out a quantitative genetic interaction analysis, as described earlier (Kawamori and Yamaguchi, 2011), using dref knockdown flies (UAS-DREF-RNAi 15 /1; sca-GAL4/1) and a loss of function allele, e2f1 rM729 . To determine this, we carried out a quantitative genetic interaction analysis, as described earlier (Kawamori and Yamaguchi, 2011), using dref knockdown flies (UAS-DREF-RNAi 15 /1; sca-GAL4/1) and a loss of function allele, e2f1 rM729 .…”
Section: Endoreplication Defects Caused By Dref Knockdown Are Partly mentioning
confidence: 99%
“…Then, why PCNA was activated with reduced levels of DREF? Length of PSC bristles were measured as detailed previously (Kawamori and Yamaguchi, 2011). In addition, E2F recognition sites in the PCNA promoter alone proved to be insufficient for promoter activity during embryonic and larval stages (Yamaguchi et al, 1995).…”
Section: Down-regulation Of Dref Stabilizes E2f1 Protein In Salivary mentioning
confidence: 99%
See 1 more Smart Citation